Days and Confused: Housing Price and Liquidity Response to New Local Public Schools. Issue 1 (2nd January 2021) - Irwin, Nicholas B.; Livy, Mitchell R.
Abstract: The existing real estate literature extensively documents the relationship between housing prices and school quality and, to a lesser extent, the effects of school quality on market liquidity. However, the capitalization and liquidity effects of new schools with unknown quality has been substantially understudied given the importance of understanding homebuyer responses to the opening of new schools. In this paper, we implement a novel three-stage least squares estimation framework to jointly examine the impact of newly opened elementary schools on housing prices and liquidity in Baltimore County, Maryland. The results provide strong evidence that homebuyers positively value these new schools through increases in prices and liquidity, despite their level of unknown quality, and the results are robust to alternative specifications and explanations. The outcomes of this research suggest future empirical work must address both price and liquidity concerns when determining the impacts of localized policies that shift school boundaries.